Native actors and filmmakers : visual storytellers - Robinson, Gary, 1950- (Native trailblazers., 2021)
Profiles twelve indigenous professionals working in the entertainment industry as actors, producers, directors, and cameramen. Discusses their lives and careers, offers advice for indigenous individuals looking to break into the industry, and includes filmographies. Back matter includes a glossary and further resources.